Influencer marketing is a new possibility to control the process of consumer’s decision acceptance about purchasing - Skryhun, Natalya; Lytka, Mariіa; Vlasenko, Ludmila (My University, 2016)
The features of influence marketing, its location in marketing activity is determined and exposed. The essence of influence marketing is considered; basic elements and values of marketing influencer for companies, and also reason of its use in practical activity of enterprises are distinguished.
Keywords: маркетинг впливу; лідери думок; influence marketing; leaders of ideas; кафедра маркетингу; кафедра іноземних мов професійного спрямування